Acute myasthenia caused by lithium: a case report - Yao, Jiashu; Ye, Ruihuan; Mao, Xihao; Jin, Mingmin; Yan, Rong; Shen, Yuedi; Dai, Ning; Chen, Wei (Frontiers in Psychiatry, 2025)
We report the case of an 18-year-old female patient with bipolar disorder who developed recurrent acute myasthenia after taking lithium. The myasthenia resolved upon discontinuation of lithium, and this occurred twice. The results of the cranial magnetic resonance imaging (MRI), multiple sleep latency test, polysomnography, ambulatory electroencephalogram (EEG), and other tests were all negative. In summary, the patient’s acute myasthenia was attributed to lithium use. Unlike previously reported cases of lithium-induced chronic and mild myasthenia symptoms, this case involved acute and widespread myasthenia with falls as the primary manifestation. The mechanism may be related to the effect of lithium on acetylcholine receptor (AChR) metabolism, neurotransmitter release, and neuromuscular junction (NMJ) stability.